2016
DOI: 10.4236/oalib.1102925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Adequacy and Utilization of Contingency Fund in Building Projects in Nigeria

Abstract: Contingency fund is allowed in the cost estimate to cater for risks which always lead to additional cost. The study used archival data to assess the accuracy of contingency sum and utilization among various types of claims. Data collected were analysed using percentile and Pearson's coefficient of correlation. The study reveals that the current allowance as contingency is 5% of the base line estimates while additional cost is 18% which implies a shortfall of 13%. Furthermore, the study shows that the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The results are aligned with those of previous findings by Aibinu et al (2002) which found that there was no well-placed strategy for forecasting contingency in Indian construction companies. The same could be a dampener for contingency objectives in addressing undefined project risk and cost overrun problems in Indian construction companies.…”
Section: Bottlenecks In Contingency Managementsupporting
confidence: 89%
See 2 more Smart Citations
“…The results are aligned with those of previous findings by Aibinu et al (2002) which found that there was no well-placed strategy for forecasting contingency in Indian construction companies. The same could be a dampener for contingency objectives in addressing undefined project risk and cost overrun problems in Indian construction companies.…”
Section: Bottlenecks In Contingency Managementsupporting
confidence: 89%
“…The study recommends the application of quantitative risks to improve the accuracy of cost contingency allowance. This observation was further endorsed by Aibinu et al, (2002) during the study on the impacts of delays on project delivery in the Nigerian construction industry. The study inferred that the distribution of contingency allowance based on assumption and perception of risks seems to be insufficient and impractical in most cases.…”
Section: Literature Reviewmentioning
confidence: 64%
See 1 more Smart Citation
“…The method is deemed to be arbitrary and undefendable (Thompson and Perry, 1992), unscientific (Chen and Hartman, 2000), and implies a degree of certainty that is not justified (Mak et al, 1998). Multiple studies have demonstrated that subjective judgments and arbitrary decisions on the amount of cost contingency are inefficient and imprecise (Akinradewo and Awodele, 2016). Despite the weaknesses of this approach, it is the most famous and used method in practice (Baccarini, 2005;Asamoah et al, 2013).…”
Section: Introductionmentioning
confidence: 99%